2017
DOI: 10.1101/lm.044164.116
|View full text |Cite
|
Sign up to set email alerts
|

Persistent effects of acute stress on fear and drug-seeking in a novel model of the comorbidity between post-traumatic stress disorder and addiction

Abstract: Even following long periods of abstinence, individuals with anxiety disorders have high rates of relapse to drugs of abuse. Although many current models of relapse demonstrate effects of acute stress on drug-seeking, most of these studies examine stressful experiences that occur in close temporal and physical proximity to the reinstatement test. Here, we assess the effects of a stressful experience in one context on fear and drug-seeking in a different context. We adapt the stress-enhanced fear learning proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Acute severe stress causes an enhanced responsiveness to mild stressors at endocrine and behavioral level. It enhances the reinforcing action of psychostimulant drugs, alcohol and opiates, and their selfadministration and resistance to extinction acutely, as well as long after the stress has ended (Piazza et al, 1989;Pizzimenti et al, 2017;Logrip et al, 2012). In most cases, a PTSD emerges first and triggers development of drug abuse and addiction.…”
Section: Self-medication For Psychiatric Disorders and Mental Problemsmentioning
confidence: 99%
“…Acute severe stress causes an enhanced responsiveness to mild stressors at endocrine and behavioral level. It enhances the reinforcing action of psychostimulant drugs, alcohol and opiates, and their selfadministration and resistance to extinction acutely, as well as long after the stress has ended (Piazza et al, 1989;Pizzimenti et al, 2017;Logrip et al, 2012). In most cases, a PTSD emerges first and triggers development of drug abuse and addiction.…”
Section: Self-medication For Psychiatric Disorders and Mental Problemsmentioning
confidence: 99%
“…relatively intense acute footshock leads to persistent enhancements in cue-induced reinstatement of methamphetamine seeking, as well as facilitating cocaine conditioned place preference (29). Furthermore, a history of exposure to a predator odor exposure enhances the reinstatement of methamphetamine seeking and exposure to stress odor also increases responding in a stress-induced reinstatement procedure (30).…”
Section: Animal Modeling Of Comorbid Ptsd and Sudsmentioning
confidence: 99%
“…The gradual effect that emerged over days is consistent with other studies of the BLA, which have found a delayed effect of BLA lesions on cue-induced reinstatement with no immediate effect on maintained cocaine self-administration (Meil and See, 1997). These and other findings suggest the importance of multiple long-term behavioral tests to reveal amygdala function in drug reward (Baxter and Murray, 2002; Pizzimenti et al, 2017).…”
Section: Discussionmentioning
confidence: 76%